2010
DOI: 10.1258/acb.2010.010020
|View full text |Cite
|
Sign up to set email alerts
|

Clinical accuracy of midnight salivary cortisol measured by automated electrochemiluminescence immunoassay method in Cushing's syndrome

Abstract: Background: The diagnosis of Cushing's syndrome (CS) represents a challenge for endocrinologists. Several screening tests are used, but none of them seems to be the gold standard for the diagnosis. The aim of this study was to confirm the diagnostic value of salivary cortisol (SC) as a first-level screening test and to evaluate the clinical performance of a electrochemiluminescence immunoassay (ECLIA) method. Methods: In 33 patients with a strong clinical suspicion of CS, we evaluated urinary free cortisol, ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 23 publications
1
25
0
8
Order By: Relevance
“…Immunoassays include the radioimmunoassay (RIA), enzyme-linked immunosorbant assay (ELISA), and automated chemiluminescence and fluorometric detection assays [11][12][13][14][15][16][17][18][19][20]. Although the detection method and automaticity of these methods vary, they are all essentially competitive binding assays using a primary antibody raised against a conjugated form of cortisol.…”
Section: Assay Methodsmentioning
confidence: 99%
“…Immunoassays include the radioimmunoassay (RIA), enzyme-linked immunosorbant assay (ELISA), and automated chemiluminescence and fluorometric detection assays [11][12][13][14][15][16][17][18][19][20]. Although the detection method and automaticity of these methods vary, they are all essentially competitive binding assays using a primary antibody raised against a conjugated form of cortisol.…”
Section: Assay Methodsmentioning
confidence: 99%
“…Finally, SC sampling is promising as samples are easy to obtain: this procedure does not require hospitalization and samples are stable up to 7 days at room temperature, and up to 1 month or more at 4°C. 19 SC reflects a free fraction of plasma cortisol and may thus be employed for a more accurate evaluation of patient monitoring during mitotane treatment. Indeed, salivary cortisol concentrations reflect unbound plasma cortisol concentrations and are therefore generally unaffected by variations in CBG values.…”
mentioning
confidence: 99%
“…Differences between presented results may be explained by different diagnostic criteria for SCS and different assay methods used. Salivary cortisol has been usually measured by RIA and ELISA [18,19,23,25,26] and much more rarely by electrochemiluminescent immunoassay (ECLIA) or liquid chromatography tandem mass spectrometry (LC-MS/ /MS) [23,27,28]. The study by Beko et al revealed better performance of LSC using ECLIA (sensitivity 100% and specificity 88%) compared to RIA (sensitivity 100% and specificity 71%) [23].…”
Section: Discussionmentioning
confidence: 99%